Analysis of curriculum management in enhancing the quality of the learning process in middle schools - Marhadi, Hendri; Kurnia, Anita; Anggraini, Helni; Nurlia, Ila; Cameliani, Viona (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Curriculum management is the process of carrying out and organizing learning activities, which requires the stages of curriculum planning, organizing the curriculum, implementing the curriculum, and evaluating the curriculum. This research aimed to analyze how curriculum management affects the quality of the learning process at SMPN 04 Bungaraya School. This research used a qualitative approach. Data collection techniques were carried out through interviews, observation, and documentation studies. The research results showed that: (1) Curriculum planning at SMPN 04 Bungaraya is carried out based on the results of student learning evaluations for each subject, assessments, education quality reports, surveys, and coordination meetings involving all school staff. (2) Organizing the curriculum at SMPN 04 Bungaraya is carried out by the principal with delegation to the deputy principal in the field of curriculum to form a curriculum team to be able to develop a curriculum that suits student needs and the challenges of contemporary education. (3) The implementation of the curriculum at SMPN 04 Bungaraya has gone well. (4) Evaluation at SMPN 04 Bungaraya is carried out through analysis of learning outcomes, use of ANBK data, and surveys of the learning environment of students, teachers, and principals to improve the quality of learning.